Non-Destructive PTR-ToF-MS Profiling of Red Delicious and Granny Smith Apple Volatilomes During Ripening - Alessia Panarese; Brian Farneti; Angelo Zanella; Iuliia Khomenko (Agriculture)
The optimal harvest date (OHD) for the long-term storage of apple fruits is of the utmost importance, not only for maintaining high quality levels, but also because the ripening stage, regulated by the autocatalytic activity of the internal ethylene concentration, greatly affects the VOCs’ synthesis. During apple ripening, chemical compounds undergo changes that affect the fruit’s overall quality, particularly its aromatic profile. Three main classes of organic molecules—aldehydes, alcohols, and esters—play a key role in these modifications. This study investigated the potential of proton transfer reaction time-of-flight mass spectrometry (PTR-ToF-MS) for the rapid, non-destructive monitoring of VOC profiles in ‘Red Delicious’ and ‘Granny Smith’ apples over a 7-week shelf-life period across three harvest dates with different ripening stages. More than 300 mass peaks in the PTR-ToF-MS spectra of the apple headspace were detected. A total of 127 of them were considered to be relevant for further analysis. Furthermore, respiration rate and IAD index were used for the non-destructive assessment of the ripening progress during the 7 weeks of shelf-life and for integrating the VOC results.